Between the therapeutic and the democratic? Mediating disability memories online - Chidgey, Red (Hagar: Studies in Society and Culture, 2014)
Disabled people constitute the "largest minority in the world" (United Nations, 2006). As such, a study of contemporary memory-making practices around disability can provide a crucial lens through which to engage with ongoing issues of socioeconomic and cultural marginalization. This article examines two digital memory projects which showcase the life stories and creative outputs of people with disabilities: the Museum of the Person USA (Bloomington, US) and Envisioning New Meanings of Disability and Difference (Toronto, Canada). I argue that a close analysis of these projects illustrates a current tension between autobiographical, self-expressive memory narratives and those orientated by wider sociopolitical claims. Significantly, gendered aspects of disability discourses also work to unsettle the boundaries of what we understand the "therapeutic" and "democratic" to be. At present there is scant research taking people with disabilities' own testimony and experience as its core sources. The rise of networked technologies and the opportunities this creates for marginal memories to be publicly shared and witnessed therefore provides a compelling context through which to examine the mediation of disability stories online, and the ways in which these memories can act as tentative resources for social justice claims.